The Development of Intelligence Learning Media for Improving Occupational Competence in Thailand Information and Digital Content Competency Level 3 - Umnapiang, Phadet (Journal of Technical Education and Training, 2022)
Occupational competency is important for preparing the workforce for growing and enhancing Thai economics in Thailand 4.0. In Thailand 4.0, new technologies and digital innovation are implemented in all sectors of daily life; consequently, intelligence learning media is needed to be developed to enhance the occupational competence of the workforce. Therefore, this research aimed (1) to develop the Intelligent Learning Media for improving occupational competence in Thailand Information and Digital Content Competency Level 3 and (2) to study the efficiency of Intelligent Learning Media for improving occupational competence in Thailand Information and Digital Content Competency Level 3. The learning media was developed by a system development life cycle integrated with artificial intelligent algorithms: Decision Tree. The accuracy of decision tree algorithms considered the quality of learning media. The result of this study showed that (1) the Intelligent Learning Media for Improved Occupational Competence in Thailand Information and Digital Content Competency Level 3 comprised four components, including TPQI competency, students’ competency, artificially intelligent algorithms, and learning media that can automatically provide and enhance students with their competency by artificially intelligent algorithms: Decision Tree, and (2) the efficacy of learning media was considered by the 95.23% correctly classified instance by a decision tree. The satisfaction of learning media was =4.38, SD=0.14.